2023
DOI: 10.3390/medicina59071236
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoking Is a Strong Predictor of Failure of Conservative Treatment in Hinchey IIa and IIb Acute Diverticulitis—A Retrospective Single-Center Cohort Study

Valentina Murzi,
Eleonora Locci,
Alessandro Carta
et al.

Abstract: Background and Objectives: Therapeutic management of patients with complicated acute diverticulitis remains debatable. The primary objective of this study is to identify predictive factors for the failure of conservative treatment of Hinchey IIa and IIb diverticular abscesses. Materials and Methods: This is a retrospective cohort study that included patients hospitalized from 1 January 2014 to 31 December 2022 at the Emergency Surgery Department of the Cagliari University Hospital (Italy), diagnosed with acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Recently, a single-centre cohort study by Murzi et al . on 71 patients with CT scan Hinchey II diverticular abscess found that tobacco smoking was the only independent predictor of conservative treatment failure [ 18 ]. Tobacco smoking can be a pathogenetic and prognostic factor through several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a single-centre cohort study by Murzi et al . on 71 patients with CT scan Hinchey II diverticular abscess found that tobacco smoking was the only independent predictor of conservative treatment failure [ 18 ]. Tobacco smoking can be a pathogenetic and prognostic factor through several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup of patients will fail the non-operative approach and require a surgical rescue strategy. Data from observational studies suggest an approximately 20–30% failure rate for both antibiotics with drainages and antibiotics alone [ 17 , 18 ]. Several studies have explored the possible factors leading to the failure of the conservative approach [ 19 , 20 ].…”
mentioning
confidence: 99%